Cognitive ability of the laboratory rat (Sprague dawley) under various lighting environments - Shani, Muhammad Farris (2016)
The study documents the cognitive ability of the laboratory rats (Sprague dawley) under various lighting environments. The group 1 rats were 7th weeks old at the starting of the experiment and the group 2 rats were 14th weeks old at the starting of the experiment were used in this experiment. Various types of light represent different light wavelength which is the fluorescent light that compose of all the wavelength of light, short wavelength light (435 nm), medium wavelength light (543 nm) and long wavelength light (611 nm). The Illuminance of 6, 12, 25, 50, 100, 200 lux was used in this study. From the experiment, the results obtained shows that the Group 1 rats were faster with the learning ability compared to the group 2 rats although not all the results shows significant difference (P>0.05). The wavelength light do show significant different (P<0.05) in the learning ability of the rats only under fluorescent light and medium wavelength light. The back-track frequency of the rat in the mazes also were recorded to indicates the memory of the rats and the results shows that the group 1 rats do more back-track frequency compare to the group 2 rats but the results is also not significantly difference. The group 2 rats learn faster as the vision of the group 2 rats was better causes the rats make the decision faster compare to the group 1 rats. The group 1 may have the degeneration process occur of their eyes vision due to the usage and the age factor. The memory of the group 1 rats was also not as good as the group 2 and the group 2 rat can remember the information longer compare to the group 1 rats. Although some of the previous experiments have indicated that there are no difference in the working memory between the older and the younger rats. In conclusion, the group 2 rats have a better learning ability and also better memory compare to the group 1. Under low wavelength light and under low light illuminance, the rat learning ability is better.